Perioperative Intravenous Lidocaine and Metastatic Cancer Recurrence - A Narrative Review - Wall, Thomas P.; Buggy, Donal J. (Frontiers in Oncology, 2021)
Cancer is a major global health problem and the second leading cause of death worldwide. When detected early, surgery provides a potentially curative intervention for many solid organ tumours. Unfortunately, cancer frequently recurs postoperatively. Evidence from laboratory and retrospective clinical studies suggests that the choice of anaesthetic and analgesic agents used perioperatively may influence the activity of residual cancer cells and thus affect subsequent recurrence risk. The amide local anaesthetic lidocaine has a well- established role in perioperative therapeutics, whether used systemically as an analgesic agent or in the provision of regional anaesthesia. Under laboratory conditions, lidocaine has been shown to inhibit cancer cell behaviour and exerts beneficial effects on components of the inflammatory and immune responses which are known to affect cancer biology. These findings raise the possibility that lidocaine administered perioperatively as a safe and inexpensive intravenous infusion may provide significant benefits in terms of long term cancer outcomes. However, despite the volume of promising laboratory data, robust prospective clinical evidence supporting beneficial anti-cancer effects of perioperative lidocaine treatment is lacking, although trials are planned to address this. This review provides a state of the art summary of the current knowledge base and recent advances regarding perioperative lidocaine therapy, its biological effects and influence on postoperative cancer outcomes.